Paleoparasitological results from XVIII century human remains from Rio de Janeiro, Brazil - Jaeger, Lauren Hubert (2013)
Paleoparasitological studies of the Brazilian colonial period are scarce. A paleoparasitological analysis was performed on human remains from the archeological site Praça XV Cemetery in Rio de Janeiro, dating from the early 18th to 19th Centuries. The samples were obtained from the Institute of the Brazilian Archaeology collection, and showed evidence of washing and brushing. Sediments were extracted from sacral foramina by scraping. Sediments from skulls were used as negative paleoparasitological controls. Spontaneous sedimentation method was performed prior to microscopic analysis. The results revealed that 8 of 10 individuals were infected with intestinal helminths and/or protozoa. Eggs of the nematodes Trichuris sp. and Ascaris sp. as well as a single taeniid egg were found. Protozoa cysts suggestive of Entamoeba sp. were also observed. Trichuris sp. was the most frequent and abundant parasite, found in 70% of individuals (26 eggs). The study showed the importance of analysis of sediment from human remains preserved in museum or scientific collections, even those subjected to a curating procedure. The levels of infection revealed here should be considered underestimations. This is the first paleoparasitological study from Rio de Janeiro city for the Brazilian colonial period and the first report of human Taenia sp. in the New World.